The reality of human resources planning in governmental universities in Riyadh City - Al-Tuwaijri, Fatima Abdulaziz; Al-Malki, Bashayer Humood; Madkali, Zahra Ali (Journal of Educational and Psychological Sciences, 2021)
This study aimed to assess the status and procedure and planning in human resources departments as well as to detect any obstacles that might hinder the planning procedure in Saudi universities in Riyadh city. To achieve that objective, the researchers used a cross-sectional descriptive methodology, and a questionnaire was used to collect the data, the population consisted of (100) HR employees, however we received (85) full responses with an 85% response rate.Following statistical analysis using an SPSS program, the results of this study showed the following:1- the average score for the planning initiative among HR departments in Saudi universities in Riyadh city was 3.31 out of 5.0 with the point (the university follows a clear policy when it comes to human resources planning by faculty members) being the least score and the point (the university provides financial support to enable the faculty members to plan human resources) being the highest score.2- the average score for the assessment of the obstacles that hinder the human resources planning was 3.2 out of 5.0 with the point (centralization of the administrative transactions in the university) being the biggest obstacle and the point (inadequate human resources electronic systems in the university) being the least perceived obstacle among participants.Study recommended:1- work to reduce the high centrality in administrative dealings in the governmental universities in Riyadh City.2-  interest in limiting the executive procedural aspect to the activities of the Human Resources Planning Department at the governmental universities in Riyadh.3-  to work for the standardization of electronic information base systems in the state universities in Riyadh.
Keywords: Planning; Human Resources; Universities; Riyadh City